Etiology and pathogenesis of duodenal mucosa lesion in chronic pancreatitis - Lyudmila Vasil'evna Vinokupova; V N Dpozdov; E V Tkachenko; I E Tpubitsyna; G G Vapvanina; L V Vinokurova; V N Drozdov; E V Tkachenko; I E Trubitsyna; G G Varvanina (Терапевтический архив, 2009)
Aim. To measure content of neuromediators (acetylcholine - Ach, serotonin - 5-NT) and gastrointestinal hormones (cholecystokinine - CCK and secretin) in the blood serum of patients with chronic pancreatitis (CP); to study protective properties of the mucus in the duodenum in CP. Material and methods. CCK and secretin concentrations were estimated by enzyme immunoassay, Ach and 5-NT were measured biochemically basally and after standard meal in 65 CP patients and in the control group. Proteolytic activity of the mucus was assessed by Ansons method. An inhibitory property of the mucus was studied by residual proteolytic activity of pepsine after its incubation with mucus. Results. In AP patients the response of biologically active substrates to standard meal changed: 5-NT concentration rose from 0.40 ± 0.07 to 0.55 ± 0.05 mcg/ml (p < 0.05) while Ach dropped from 1.7 ± 0.3 to 1.6 ± 0.3 mmol/l (p > 0.05). BP patients responded to the standard meal with 5-HT concentration rise from 0.28 ± 0.04 to 0.43 ± 0.05 mcg/ml (p < 0.05), Ach changed insignificantly (from 1.5 ± 0.12 to 1.45 ± 0.21 mmol/l, p > 0.05, reslectively). CCK after standard meal significantly rose both in AP and BP. AP and BP patients had strong direct correlation between concentrations of 5-HT and CCK (r = 0.875439) and weak negative correlation with Ach level (r = -0.2209). In AP and BP patients secretin level weakly negatively correlated both with 5-NT and Ach levels (r = -0.4839 and r = -0.33207, respectively). Reduction of secretin secretion diminished secretion of bicarbonates and mucus with simultaneous change in the quality of mucous gel. Conclusion. In CP of various etiology there are changes in the level and proportions of neuromediators and hormones causing alterations in the regulation system. These disorders correlate with disturbances in pancreatic excretory function and destructive tissue changes. Bicarbonates secretion decreases and changes quality of the secreted mucus.